XIX ASR OXIRI XX ASRLARDA URGUT ETNOGRAFIYASI - Usmonov Suxrob Hasan oʻgʻli (Journals Park Publishing, 2023)
This article is devoted to the ethnography of the city of Urgut in Uzbekistan during the late 19th and 20th centuries. It analyzes the social and cultural aspects of the city's population, including their traditional practices and beliefs, economic activities and social organization. The study is based on primary sources, including ethnographic data and historical records. The results provide insight into Urgut's complex cultural and social dynamics and shed light on the changes that took place in the city in the 20th century.
Keywords: ethnography, Urgut, Uzbekistan, social organization, traditional practice, cultural dynamics, economic activity, primary sources.